Effects of structured patient education in adults with atopic dermatitis: multicenter randomized controlled trial - Heratizadeh, Annice; Schäkel, Knut; Weisshaar, Elke (The journal of allergy and clinical immunology, 2017)
Background: Atopic dermatitis (AD) is a chronic relapsing skin disease prevalent in 1% to 3% of adults in Western industrialized countries. Objective: We sought to investigate the effectiveness of educational training in an outpatient setting on coping with the disease, quality of life, symptoms, and severity in adults with AD. Methods: In this German prospective, randomized controlled multicenter study, adult patients with moderate-to-severe AD were educated by referring to a comprehensive 12-hour training manual consented by a multiprofessional study group from different centers (Arbeitsgemeinschaft Neurodermitisschulung für Erwachsene [ARNE]). Patients were randomly allocated to the intervention or waiting control groups. Study visits were performed at baseline and after 1 year (1 year of follow-up). Primary outcomes were defined as a decrease in (1) “catastrophizing cognitions” with respect to itching (Juckreiz-Kognitions-Fragebogen questionnaire), (2) “social anxiety” (Marburger Hautfragebogen questionnaire), (3) subjective burden by symptoms of the disease (Skindex-29 questionnaire), and (4) improvement of disease signs and symptoms assessed by using the SCORAD index at 1 year of follow-up. Data were analyzed on an intention-to-treat basis. Results: At 1 year of follow-up, patients from the intervention group (n = 168) showed a significantly better improvement compared with the waiting group (n = 147) in the following defined primary study outcomes: coping behavior with respect to itching (P < .001), quality of life assessed by using the Skindex-29 questionnaire (P < .001), and the SCORAD index (P < .001). Conclusions: This is the first randomized, controlled multicenter study on patient education in adult AD. The ARNE training program shows significant beneficial effects on a variety of psychosocial parameters, as well as AD severity.